A Structural Description of Mood-Tense Systems of Armenian Dialects - GEVORKYAN, GAYANE (Bulletin of Yerevan University B: Philology, 2021)
There are different tense and mood structural models in Armenian territorial variants (dialects and subdialects). As a result of their contrastivecomparative analysis, it becomes clear, that the synthetic tense forms of positive conjugation prevail over the ones that have analytical forms (correlation 21/12), whereas in the negative conjugation there is the opposite tendency: the mood forms with synthetic structure are fewer that the ones with analytical structure (correlation 9/17).
Keywords: structural model, synthetic form, analytical form, positive conjugation, negative conjugation, territorial variant, contrastive-comparative analyse